(untitled) (Global Journal of Medical Research, 2016)
Haemoparasitic diseases account for substantial losses in terms of decreased working capacity, growth and productivity of camels. A survey of the one humped camel (Camelus dromedarius) slaughtered in Maiduguri was conducted from January to June, 2016 to determine the prevalence of haemoparasites and their effects on some haematological parameters. Blood samples were randomly collected from 209 camels at the point of slaughter and subjected to standard haematological procedures to determine the white blood cell count (WBC), packed cell volume (PCV), heamoglobin concentration (Hb), mean corpuscular volume (MCV), mean corpuscular heamoglobin (MCH) and mean corpuscular heamoglobin concentration (MCHC). Blood films and Giemsa stained thin smears were prepared on clean glass slides and examined for the presence of haemoparasites. Haemoparasites were identified microscopically to generic level based on morphological features. A total prevalence of 12.6% was recorded for Anaplasma (37.7%), Trypanosoma (33.3%) and Babesia (22.2%), in addition to microfilariae of Dipetalonema species (7.5%).